Análise do uso do termo de consentimento livre e esclarecido (TCLE) por cirurgiões-dentistas que executam tratamento restaurador - Rodrigues, Lívia Graziele (2016)
The aim of this study was to evaluate the knowledge of dentists that perform restorative treatment about the Consent Informed (CI) used in your dental clinical practice and to collect data that would allow subsidize the construction of an CI that can be used in this practice dental. For this, a structured questionnaire was applied to Dentists who perform restorative treatment in order to make a diagnosis of use of relationship and knowledge of the importance of informed consent. After distributing 731 questionnaires, 179 professionals returned these questionnaires. Of the respondents, 169 said that the discipline of forensic dentistry was studied for them at graduation, 128 studied the subject of Ethics and Law for graduate school, 139 received lessons on the importance and composition of CI in restorative practice, and 171 of them claim give verbal explanations of treatment for patients. However, 67 of these professionals do not use the CI, but 165 of all respondents believe that the use of this document may endorse the Dentists in a possible lawsuit. When asked about what information should be explicit in the CI, 157 of these professionals felt it necessary to contain the risks inherent in the type of treatment; 150, the limitations of the case; 138, the obligations of the patient; 85, treatment costs and 76 stages of the restorative treatment. The Dentists also said they talk to their patients about risks or needs associated with restorative treatment, and 143 professionals talk about tooth sensitivity; 140, need for endodontic treatment; 141, risk of restoration fracture / facet; 127, decay; 71, pulp necrosis and 66 dental darkening. These findings showed that although many of the interviewees possess some level of knowledge of the importance of the use of this document, 67 professionals do not use in their clinical practice. However, most of them fulfills the requirements of the Consumer Protection Code (CDC) and the Dental Code of Ethics (CEO), providing verbal explanations of treatment to patients.